2008
DOI: 10.1016/j.ecl.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Craniopharyngiomas

Abstract: Craniopharyngiomas are epithelial tumors arising along the path of the craniopharyngeal duct and presenting with a variety of manifestations. Their optimal management remains a subject of debate. Currently, surgical excision followed by external beam irradiation is the main treatment option. Craniopharyngiomas are associated with significant long-term morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 121 publications
(197 reference statements)
0
35
1
5
Order By: Relevance
“…67,93 These tumors are generally well circumscribed and rarely contain calcifications on neuroimaging. 23,45,93 Histologically they consist of mature squamous epithelium and pseudopapillae, often appearing similar to Rathke cleft cysts that have undergone squamous differentiation at their epithelial lining. 23 Macroscopically they can have solid and/or cystic components, with cystic contents that are yellow and viscous.…”
Section: Subtypes Of Craniopharyngiomamentioning
confidence: 99%
“…67,93 These tumors are generally well circumscribed and rarely contain calcifications on neuroimaging. 23,45,93 Histologically they consist of mature squamous epithelium and pseudopapillae, often appearing similar to Rathke cleft cysts that have undergone squamous differentiation at their epithelial lining. 23 Macroscopically they can have solid and/or cystic components, with cystic contents that are yellow and viscous.…”
Section: Subtypes Of Craniopharyngiomamentioning
confidence: 99%
“…Patients with these tumors often present with impaired pituitary function. 33 Reported rates for anterior pituitary hormone deficits prior to any operative intervention vary from 35 to 95% for growth hormone, 38 to 82% for follicle-stimulating hormone/luteinizing hormone, 21 to 62% for corticotrophin, and 21 to 42% for thyroid-stimulating hormone. 32 Authors of large patient series have reported that between 6 and 38% of patients present with insufficient secretion of antidiuretic hormone.…”
mentioning
confidence: 99%
“…16 Its estimated incidence is 13 cases per 1 million individuals/year. 11,13 The ideal method of treatment remains highly controversial. However, a gross-total resection is thought to be associated with the best outcomes regarding postsurgical recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%